Assessment of Iron Reserves: Association of Serum Ferritin with Red Blood Cell Indices - Zulfiqar, Kiran (International Journal of Pathology, 2019)
Background: Iron deficiency is one of the major nutritional deficiency diseases of developing countries. Females are at higher risk of developing Iron deficiency in reproductive years of life. Usually serum Ferritin gives us good estimate of iron status in the body. However, this biomarker is not in the reach of the poor patients and falsely rises in inflammatory conditions.Objective: To assess and correlate serum ferritin with easily accessible red cell indices in females of reproductive age in district Faisalabad to determine if the latter alone are sufficient to make diagnosis of iron deficiency anemiaMethods: 199 females aged 13-45 years were enrolled in the study after written informed consent. Pregnant females and those suffering from acute or chronic illnesses were excluded. Blood was drawn in plain tube to assess serum Ferritin, Iron and Total Iron binding capacity, EDTA plasma tube was used for the analysis of red cell indices mean cell volume, mean hemoglobin concentration and red cell distribution widthResults: Based on lone Hemoglobin levels, Anemia was found in 77/101(75.81%) of population. Of these 77 anemic subjects, 52(67.53%) had iron deficiency. Low serum ferritin level was observed in 60 (59.40%) of total females. Among low ferritin subjects, 10 % (6/60) had normal hemoglobin levels. Significant positive correlation was observed between serum ferritin and MCV (r=0.709=; P=<0.001), MCHC (r=0.729=; P=0.001) and significant negative correlation was seen between Serum ferritin and RDW (r=0.676; P=0.001). No significant correlation was appreciated between serum ferritin and MCH. The main cause of iron deficiency was determined as use of iron deficient diet followed by repeated pregnancies.Conclusions: A substantial proportion 57.42% (58) of females of reproductive age years was suffering from Iron deficiency in district Faisalabad. MCV, MCHC and RDW may still be used as indicators of Iron deficiency in places where serum ferritin is not available or patients cannot afford and when there is any associated inflammatory condition